25 Chants d'Ecole - Camauër, Godefroid 1821-1884 Père; Delarge, Jean-Guillaume 1829-1886 (Huy Felder-Delloye)
25 Morceaux
Embossed stamp of the composer on title page
Autographe dedication by the composer on title page
Keywords: 19th Century (1801-1900); Song; Music education; Wallonia (Belgium)